Green product innovation, R&D, and AI adoption: The moderating role of intellectual capital in achieving competitive advantage - Wahyudi, Tri; Arisondha, Edy; Bin Bakar, Mohd Hafiz; Soleha, Nurhayati (Journal of Accounting and Investment, 2025)
Research aims: This study investigates the impact of green product innovation, R&D investment, and AI adoption on competitive advantage, with intellectual capital examined as a moderating variable.Design/Methodology/Approach: Data were collected from 150 respondents representing 60 manufacturing firms in Indonesia. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0.Research findings: Green product innovation, R&D investment, and AI adoption significantly and positively influence competitive advantage. Intellectual capital strengthens the effects of green innovation and R&D investment but does not significantly moderate the effect of AI adoption.Theoretical contribution/ Originality : This research extends the Resource-Based View (RBV) by integrating green innovation, R&D investment, AI adoption, and intellectual capital into competitive advantage models, while emphasizing management accounting perspectives within emerging market contexts.Practitioner/Policy implication: The study highlights the need for firms to develop not only innovation initiatives but also robust intellectual capital infrastructures to sustain competitive advantage.Research limitation/Implication: The study is limited by its cross-sectional design and traditional conceptualization of intellectual capital, suggesting opportunities for longitudinal studies and digital capability-focused research.